Danger and death: organisational and occupational responses to the murder of police in South Africa - a case study - Perkins, Gráinne (Department of Public Law, 2019)
Danger has long been assumed a critical feature of the occupational identity of police officials. Much of the scholarly literature on the topic has been dominated by research originating in Europe and the United States. This study draws inspiration from the literature of the global North but investigates danger and death in a Southern locality. South Africa provides a case study for an exploration of danger and death as perceived, experienced and acted upon by a police institution with long-standing paramilitary origins and one that continues to confront high rates of violent crime in contemporary South Africa. In comparative terms South Africa continues to exhibit high rates of police homicide. Research into the context within which such homicides occur, the associative factors that accompany danger and death and the impact thereof on subcultural identity and operational responses remain under-investigated. This thesis attempts to fill this gap by examining how danger and death are perceived, experienced and acted upon by police officials across three units in a police station located in an urban settlement situated on the fringe of Cape Town. The inquiry draws on the conceptual work of Michel Foucault, Pierre Bourdieu and Theodore Sarbin, and utilises both quantitative and qualitative research methods. An analysis of investigative files of police murders in the Western Cape combined with observation of memorial services and extensive participant observation of three police units in a high-crime area of urban settlement, yielded rich data. The research concludes that police construct danger as much as danger, as an objective reality, shapes the police’s experience of danger and their responses to danger. Danger can be said to have both an objective and subjective reality – it is at once constituted and constitutive. The findings illustrate that danger is given material effect through risk reduction strategies; that danger is dramatised through its memorialisation and that danger is normalised and routinised in everyday police practices. Responses to danger and police murder vary from formal or organisational to informal or occupational responses. The relationship between organisational (formal) responses and occupational (informal) responses is complex - there is evidence of both overlap and contradiction to be found in that relationship.